Application of Artificial Intelligence in Graphical Discrimination of Structural Cracks - Ren-Jwo Tsay (Engineering proceedings, 2025)
For the detection of structural cracks, engineers need to conduct measurements on-site. However, structural cracks are widely distributed and are not easy to access for measurement. Therefore, photography is commonly used for crack detection. Although the crack is observed in the photos, its location and size need to be clearly defined. Artificial intelligence (AI) and databases are used in graphic processing methods to perform structural crack analysis, in which the Python 3.12 program is used as the main tool. Using the Python program, an AI image analysis program was developed for crack analysis and evaluation. ChatGPT 3.5 was also used for the analysis of crack length and width. Using AI considerably increased credibility in detecting and measuring structural cracks.